Pregnancy Downregulates Plasmablast Metabolic Gene Expression Following Influenza Without Altering Long-Term Antibody Function - Swieboda, Dominika; Littauer, Elizabeth Q.; Beaver, Jacob T.; Mills, Lisa K.; Bricker, Katherine M.; Esser, E. Stein; Antao, Olivia Q.; Williams, Dahnide T.; Skountzou, Ioanna (Frontiers in Immunology, 2020)
While the majority of influenza-infected individuals show no or mild symptomatology, pregnant women are at higher risk of complications and infection-associated mortality. Although enhanced lung pathology and dysregulated hormones are thought to underlie adverse pregnancy outcomes following influenza infection, how pregnancy confounds long-term maternal anti-influenza immunity remains to be elucidated. Previously, we linked seasonal influenza infection to clinical observations of adverse pregnancy outcomes, enhanced lung and placental histopathology, and reduced control of viral replication in lungs of infected pregnant mothers. Here, we expand on this work and demonstrate that lower infectious doses of the pandemic A/California/07/2009 influenza virus generated adverse gestational outcomes similar to higher doses of seasonal viruses. Mice infected during pregnancy demonstrated lower hemagglutination inhibition and neutralizing antibody titers than non-pregnant animals until 63 days post infection. These differences in humoral immunity suggest that pregnancy impacts antibody maturation mechanisms without alterations to B cell frequency or antibody secretion. This is further supported by transcriptional analysis of plasmablasts, which demonstrate downregulated B cell metabolism and post-translational modification systems only among pregnant animals. In sum, these findings corroborate a link between adverse pregnancy outcomes and severe pathology observed during pandemic influenza infection. Furthermore, our data propose that pregnancy directly confounds humoral responses following influenza infection which resolves post-partem .Additional studies are required to specify the involvement of plasmablast metabolism with early humoral immunity abnormalities to best guide vaccination strategies and improve our understanding of the immunological consequences of pregnancy.